Chronic effects of air pollution on respiratory health in Southern California children: findings from the Southern California Children’s Health Study - Chen, Zhanghua (J Thorac Dis, 2015)
Outdoor air pollution is one of the leading contributors to adverse respiratory health outcomes in urban areas around the world. Children are highly sensitive to the adverse effects of air pollution due to their rapidly growing lungs, incomplete immune and metabolic functions, patterns of ventilation and high levels of outdoor activity. The Children’s Health Study (CHS) is a continuing series of longitudinal studies that first began in 1993 and has focused on demonstrating the chronic impacts of air pollution on respiratory illnesses from early childhood through adolescence. A large body of evidence from the CHS has documented that exposures to both regional ambient air and traffic-related pollutants are associated with increased asthma prevalence, new-onset asthma, risk of bronchitis and wheezing, deficits of lung function growth, and airway inflammation. These associations may be modulated by key genes involved in oxidative-nitrosative stress pathways via gene-environment interactions. Despite successful efforts to reduce pollution over the past 40 years, air pollution at the current levels still brings many challenges to public health. To further ameliorate adverse health effects attributable to air pollution, many more toxic pollutants may require regulation and control of motor vehicle emissions and other combustion sources may need to be strengthened. Individual interventions based on personal susceptibility may be needed to protect children’s health while control measures are being implemented.